2021
DOI: 10.3390/jcm10051009
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implant Bone Loss Measurement Using a Region-Based Convolutional Neural Network on Dental Periapical Radiographs

Abstract: Determining the peri-implant marginal bone level on radiographs is challenging because the boundaries of the bones around implants are often unclear or the heights of the buccal and lingual bone levels are different. Therefore, a deep convolutional neural network (CNN) was evaluated for detecting the marginal bone level, top, and apex of implants on dental periapical radiographs. An automated assistant system was proposed for calculating the bone loss percentage and classifying the bone resorption severity. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 38 publications
0
29
2
1
Order By: Relevance
“…3 ). These findings differed from those of Cha et al [ 28 ], whose dataset included various implants with different implant-abutment junctions. In that study, the most coronal thread of the implant was used as a threshold position.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…3 ). These findings differed from those of Cha et al [ 28 ], whose dataset included various implants with different implant-abutment junctions. In that study, the most coronal thread of the implant was used as a threshold position.…”
Section: Discussioncontrasting
confidence: 99%
“…The inclusion criteria were as follows: periapical radiographs of dental implants, appropriate radiation exposure, and radiographs of dental implants acquired in parallel. The exclusion criteria were as follows: excessively bright or dark images precluding distinguishment of marginal bone around dental implants, severely distorted images of dental implants, and/or graft material hindering observation of the alveolar bone [ 28 ]. Each digital radiograph was exported with a resolution of 96 dpi and size of approximately 300–500 × 300–400 pixels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] Recently, emerging studies showed that AI can be used in orthopaedics. [31][32][33] For example, Yeh et al 30 showed that an AI-baed automatic alignment measure system can locate spinal anatomic landmarks with a high accuracy and produce radiographic parameters that correlated well with operator-based measurements. Yabu et al 34 also demonstrated that convolutional neural network could detect new osteoporotic vertebral fractures utilising magnetic resonance images with performance comparable to that of spine surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Además, se desarrollaron la DCNN y CNN (google net, inception V3 para la clasificación de los implantes dentales 14 siendo altamente efectivo en clasificar implantes de formas similares de diferentes tipos de implantes en comparación con odontólogos. Así mismo, para detectar periimplantitis Cha et al 15 utilizaron CNN, no encontrando diferencia significativa entre el modelo CNN y el de periodoncistas. También se ha analizado la detección y clasificación de fracturas de los implantes utilizando 3 DCNN (convolutional neural network (DCNN) architectures (VGGNet-19, GoogLeNet, Inception.V3 and automated DCNN) 16 con una precisión de 0,80.…”
Section: Revisión Y Discusiónunclassified